The Circulation of Agency in E-Justice
XXI, 365 p. 35 illus., 30 illus. in color.
Keywords: This book contributes to an understanding of the dynamic complexities involved in the design of e-justice applications that enable online trans-border judicial proceedings in Europe. It provides answers to critical questions with practical relevance: How should online trans-border judicial proceedings be designed in order to deliver effective and timely justice to European citizens, businesses and public agencies? How can the circulation of judicial agency across Europe be facilitated? Based on extensive research, the book explores and assesses the complex entanglements between law and technology, and between national and European jurisdictions that emerge when developing even relatively simple e-services such as those supporting the European small claims procedure and European payment orders. In addition to providing a strong theoretical framework and an innovative approach to e-justice design, this book includes case studies that are based on a common methodology and theoretical framework. It presents original empirical material on the development of e-government systems in the area of European justice. Finally, it introduces the design strategies of Maximum Feasible Simplicity and Maximum Manageable Complexity and, based on them, it proposes architectural and procedural solutions to enhance the circulation of judicial agency.